Aquaculture technology toolkit catalogue: clearinghouse technical report series 012 - Technologies for African Agricultural Transformation (Technologies for African Agricultural Transformation, 2022)
This catalogue describes a series of technologies related to the modernization of aquaculture in Africa. It is developed through a collaborative effort from the Technologies for African Agricultural Transformation (TAAT) program from the African Development Bank that seeks to increase stakeholder usage of proven agricultural technology, and its Aquaculture Compact project partners. The compilation is also supported by the Project Platform for Agricultural Solutions (ProPAS), an information portal where innovations are systematically characterized for open access. Both activities address the imperative to better connect proven technologies to those who need them, but each undertakes this goal differently. Aquaculture is one of nine commodity compacts with proven technologies that have the potential to ensure self-sufficiency in fish production and increase yields and benefits for upscaling. Fish is also targeted as an agro-industrial commodity for processing and trading on domestic and regional markets. The TAAT Aquaculture Compact, led by WorldFish, informs a wide variety of stakeholders through capacity development and technological outreach, and 2 this catalogue assists them in doing so. The countries targeted by the Aquaculture Compact are Benin, Burundi, Cameroon, Cote d'Ivoire, Democratic Republic of Congo, Ghana, Kenya, Malawi, Nigeria, Tanzania, Togo, and Zambia. The TAAT Program identified proven technologies that advance fish production and we have compiled them into a “Toolkit Catalogue” meant to promote understanding and stimulate adoption and investment. This is one of several such catalogues produced as a joint TAAT-ProPAS activity. For more information on the featured technologies or other solutions for the transformation of aquaculture in Sub-Saharan Africa, contact Prof. Bernadette Fregene at b.fregene@cgiar.org.